HPTLC Method Development and Validation of Secondary Metabolite-Thymol from Sufof-E-Mohazzil: A Unani Formulation - G. Patil, Avinash; Y. Ansari, Aqsa; P. Koli, Swapneel; A. Patil, Darshana (Asian Journal of Chemistry, 2013)
Chromatographic techniques can be used to document phytochemical fingerprints and quantitate chemical markers in the herbal raw material. Sufoof-e-mohazzil (SM) is one of the most trusted and sold Unani formulation. Sufoof-e-mohazzil which has been used in Unani Pharmacy since antiquity is used as antiobesity agent, digestive and for controlling high cholesterol levels. Thymol as phytochemical marker was quantified using HPTLC from in-house and two marketed formulations (SM-1 and SM-2) of Sufoof-e-mohazzil. Quantification was carried out on silica gel 60 F254 pre-coated HPTLC plates using toluene: ethyl acetate: GAA [97:3:0.2, (v/v/v)] as mobile phase. The response was linear over the range of 1 μg/mL to 5 μg/mL with correlation coefficient of 0.986. Accuracy of the method was checked by recovery studies at three different levels and the average percentage recoveries were found to be 97.94 ± 0.5. The concentration of the thymol was found to be 2.780 μg/mL for in-house formulation whereas 2.180 and 1.768 μg/mL for SM-1 and SM-2 respectively. The method was validated for linearity, precision, accuracy and ruggedness and can be used for routine quality control of Unani formulation Sufoof-e-mohazzil.